Long-Run Relationship Between Personal Housing Loan and Economic Growth - Mekvatana, Komol; Rangkakulnuwat, Poomthan (Asian Journal of Applied Economics, 2017)
This research aims to study long-run equilibrium relationship between economic growth and personal housing loans along with macroeconomic variables of Thailand under the concept of Endogenous Growth Theory. The results found long-run equilibrium relationship between real GDP, gross fixed capital formation, internet user, net foreign direct investment, real interest rate, and personal housing loans. The long-run equilibrium relationship is consistent to Endogenous Growth Theory, where gross fixed capital formation, internet user, net foreign direct investment and real estate credits have positive effect to output in the long-run; while real interest rate has negative effect to output in the long-run. That is personal housing loan can be adopted as long-run stimulus policy. Furthermore, the higher in internet access can stimulate economic growth in the long-run.